2012
DOI: 10.1136/jclinpath-2011-200455
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic prostatic tissue in the uterine cervix. Report of a case and brief overview of basaloid cervical glandular lesions

Abstract: Figure 3 Ectopic prostatic tissue, medium power. Insert high-molecular weight keratin (34bE12).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Prostatic-type tissue in the female genital tract is a phenomenon first described in the uterine cervix in 1997, 90 with subsequent literature expanding the clinicopathologic picture of the lesions. [91][92][93][94][95][96][97][98][99][100] The prostatic-type tissue is composed of glands identical in morphology and immunohistochemical staining to male prostatic glands, and frequently lined by basal cells (Figure 7, A). Early studies reported the presence of prostatic glands within the lamina propria of the uterine cervix, sparing the squamous epithelium, but with frequent and often extensive squamous metaplasia in the prostatic-type glands, with the potential for misdiagnosis as squamous cell carcinoma when identified deep within the stroma (Figure 7, B through D).…”
Section: Ectopic Prostate Tissue (Prostatic Metaplasia)mentioning
confidence: 99%
See 4 more Smart Citations
“…Prostatic-type tissue in the female genital tract is a phenomenon first described in the uterine cervix in 1997, 90 with subsequent literature expanding the clinicopathologic picture of the lesions. [91][92][93][94][95][96][97][98][99][100] The prostatic-type tissue is composed of glands identical in morphology and immunohistochemical staining to male prostatic glands, and frequently lined by basal cells (Figure 7, A). Early studies reported the presence of prostatic glands within the lamina propria of the uterine cervix, sparing the squamous epithelium, but with frequent and often extensive squamous metaplasia in the prostatic-type glands, with the potential for misdiagnosis as squamous cell carcinoma when identified deep within the stroma (Figure 7, B through D).…”
Section: Ectopic Prostate Tissue (Prostatic Metaplasia)mentioning
confidence: 99%
“…Early studies reported the presence of prostatic glands within the lamina propria of the uterine cervix, sparing the squamous epithelium, but with frequent and often extensive squamous metaplasia in the prostatic-type glands, with the potential for misdiagnosis as squamous cell carcinoma when identified deep within the stroma (Figure 7, B through D). [90][91][92][93][94]100 In some cases, the squamous component almost entirely obscures the glandular component. Most cases in these early studies were identified incidentally during evaluation of squamous intraepithelial lesions, with rare presentation as a clinically identified mass.…”
Section: Ectopic Prostate Tissue (Prostatic Metaplasia)mentioning
confidence: 99%
See 3 more Smart Citations